Reversal of murine alcoholic steatohepatitis by pepducin-based functional blockade of interleukin-8 receptors. Issue 5 (8th February 2016) - Wieser, Verena; Adolph, Timon E; Enrich, Barbara; Kuliopulos, Athan; Kaser, Arthur; Tilg, Herbert; Kaneider, Nicole C
Abstract : Objective: Alcoholic steatohepatitis is a life-threatening condition with short-term mortality up to 40%. It features hepatic neutrophil infiltration and blood neutrophilia, and may evolve from ethanol-induced breakdown of the enteric barrier and consequent bacteraemia. Signalling through CXCR1/2 G-protein-coupled-receptors (GPCRs), the interleukin (IL)-8 receptors, is critical for the recruitment and activation of neutrophils. We have developed short lipopeptides (pepducins), which inhibit post-ligand GPCR activation precisely targeting individual GPCRs. Design: Experimental alcoholic liver disease was induced by administering alcohol and a Lieber–DeCarli high-fat diet. CXCR1/2 GPCRs were blocked via pepducins either from onset of the experiment or after disease was fully established. Hepatic inflammatory infiltration, hepatocyte lipid accumulation and overall survival were assessed as primary outcome parameters. Neutrophil activation was assessed by myeloperoxidase activity and liver cell damage by aspartate aminotransferase and alanine aminotransferase plasma levels. Chemotaxis assays were performed to identify chemoattractant signals derived from alcohol-exposed hepatocytes. Results: Here, we show that experimental alcoholic liver disease is driven by CXCR1/2-dependent activation of neutrophils. CXCR1/2-specific pepducins not only protected mice from liver inflammation, weight loss and mortality associated with experimental alcoholic liver disease, but therapeutic administration cured disease and prevented further mortality in fully established disease. Hepatic neutrophil infiltration and triglyceride accumulation was abrogated by CXCR1/2 blockade. Moreover, CXCL-1 plasma levels were decreased with the pepducin therapy as was the transcription of hepatic IL-1β mRNA. Conclusions: We propose that high circulating IL-8 in human alcoholic hepatitis may cause pathogenic overzealous neutrophil activation, and therapeutic blockade via pepducins merits clinical study.